Ion mobility spectrometry – Mass spectrometry coupling for synthetic polymers. (11th February 2020) - Charles, Laurence; Chendo, Christophe; Poyer, Salomé
Abstract : This review covers applications of ion mobility spectrometry (IMS) hyphenated to mass spectrometry (MS) in the field of synthetic polymers. MS has become an essential technique in polymer science, but increasingly complex samples produced to provide desirable macroscopic properties of high‐performance materials often require separation of species prior to their mass analysis. Similar to liquid chromatography, the IMS dimension introduces shape selectivity but enables separation at a much faster rate (milliseconds vs minutes). As a post‐ionization technique, IMS can be hyphenated to MS to perform a double separation dimension of gas‐phase ions, first as a function on their mobility (determined by their charge state and collision cross section, CCS), then as a function of their m/z ratio. Implemented with a variety of ionization techniques, such coupling permits the spectral complexity to be reduced, to enhance the dynamic range of detection, or to achieve separation of isobaric ions prior to their activation in MS/MS experiments. Coupling IMS to MS also provides valuable information regarding the 3D structure of polymer ions in the gas phase and regarding how to address the question of how charges are distributed within the structure. Moreover, the ability of IMS to separate multiply charged species generated by electrospray ionization yields typical IMS‐MS 2D maps that permit the conformational dynamics of synthetic polymer chains to be described as a function of their length.